The In Situ Observation of Phase Transformations During Intercritical Annealing of a Medium Manganese Advanced High Strength Steel by High Energy X-Ray Diffraction - Hu, Xiaohua; Mueller, Josh J.; Sun, Xin; De Moor, Emmanuel; Speer, John G.; Matlock, David K.; Ren, Yang (Frontiers in Materials, 2021)
Microstructural changes during thermal processing of a medium manganese steel containing (in wt%) 0.19C and 4.39 Mn were evaluated in situ with a high energy X-ray diffraction system (HEXRD). Samples with an initial fully martensitic microstructure were heated to intercritical annealing (IA) temperatures of 600 or 650°C, held for 30 min, and cooled to room temperature. Diffraction data were analyzed to determine the variations in austenite and ferrite phase fractions and phase lattice constants throughout the ICA cycles. On heating, the 2 vol. pct of austenite present in the starting microstructure decomposed, and cementite precipitation then occurred. During isothermal holding, the austenite fraction increased, up to 20% for the sample annealed at 650°C. The measured austenite fractions were less than those calculated by Thermo-Calc for equilibrium conditions, indicating that the 30-min hold time was insufficient to achieve near-equilibrium conditions. Observed changes in lattice parameters during isothermal holding were interpreted to reflect composition changes due to redistribution of the C and Mn between austenite and ferrite. The results are discussed in relation to the potential for controlling austenite stability during ambient temperature deformation.